Statistical analysis and optimization of recovering indium from jarosite residue with vacuum carbothermic reduction by response surface methodology (RSM) - Ma Hongzhou (Green Processing and Synthesis, 2017)
Vast jarosite residue was produced from traditional zinc hydrometallurgy process in China. It is necessary to recover valuable metals from the jarosite residue. Indium is the one of them. Recovering indium from jarosite residues with carbon reduction method under the condition of vacuum was investigated. The analysis of variance was used to evaluate the influence of different factors on the volatilizing rate of indium, indicating that the influence of temperature on the volatilizing rate of indium is statistically significant. Other factors have no significant influence. Response surface methodology was used to explore the best combination of four variables and to study the effects of their interactions on the indium volatilizing rate. The results showed that there was an obvious interaction between the percent content of carbon and temperature and between the percent content of carbon and hold time, and the selected optimal conditions were 30% carbon, 13% CaO, 1000°C temperature, and 60 min hold time. Under these conditions, the indium volatilization rate was up to 98.2%.